The double‐edged sword of systemic corticosteroid therapy in viral pneumonia: A case report and comparative review of influenza‐associated mucormycosis versus COVID‐19 associated mucormycosis. Issue 8 (5th March 2021) - Ahmadikia, Kazem; Hashemi, Seyed Jamal; Khodavaisy, Sadegh; Getso, Muhammad Ibrahim; Alijani, Neda; Badali, Hamid; Mirhendi, Hossein; Salehi, Mohammadreza; Tabari, Azin; Mohammadi Ardehali, Mojtaba; Kord, Mohammad; Roilides, Emmanuel; et al.
Abstract: Acute respiratory distress syndrome is a common complication of severe viral pneumonia, such as influenza and COVID‐19, that requires critical care including ventilatory support, use of corticosteroids and other adjunctive therapies to arrest the attendant massive airways inflammation. Although recommended for the treatment of viral pneumonia, steroid therapy appears to be a double‐edged sword, predisposing patients to secondary bacterial and invasive fungal infections (IFIs) whereby impacting morbidity and mortality. Mucormycosis is a fungal emergency with a highly aggressive tendency for contiguous spread, associated with a poor prognosis if not promptly diagnosed and managed. Classically, uncontrolled diabetes mellitus (DM) and other immunosuppressive conditions including corticosteroid therapy are known risk factors for mucormycosis. Upon the background lung pathology, immune dysfunction and corticosteroid therapy, patients with severe viral pneumonia are likely to develop IFIs like aspergillosis and mucormycosis. Notably, the combination of steroid therapy and DM can augment immunosuppression and hyperglycaemia, increasing the risk of mucormycosis in a susceptible individual. Here, we report a case of sinonasal mucormycosis in a 44‐year‐old woman with hyperglycaemia secondary to poorly controlled diabetes following dexamethasone therapy on a background of influenza pneumonia and review 15 available literatures on reported cases of influenza and COVID‐19 associated mucormycosis.